Three-phase harmonics measurement method based on mSDFT - Carugati, Ignacio (2014)
This work presents a three-phase harmonics measurement method based on the mSDFT (Modulated Sliding Discrete Fourier Transform) and a variable sampling period technique. The proposal allows measuring the harmonic components of a three-phase signal and computes the corresponding imbalance by estimating its positive, negative and zero sequence. In addition, an adaptive variable sampling period is used in order to obtain a sampling frequency multiple of the main frequency. mSDFT high rejection to distortions in the electrical network and flexibility of proposed method makes it an interesting alternative for the design of grid power monitors.